MODEL PEMBERDAYAAN ZAKAT PRODUKTIF LAZISMU SOLO - Imron Rosyadi (Universitas Muhammadiyah Surakarta, 2020)
Poverty has been a problem for the people since ancient times. Various efforts have been made by many groups, both individuals and institutions. This study is to determine the model of management, implementation, and utilization of productive zakat that is carried out by Lazismu Solo to provide welfare and justice. This research can be categorized into field research, because the object is the utilization of productive zakat which is carried out by Lazismu Solo.From the discussion and analysis that has been described, it can be concluded that the implementation of productive zakat utilization carried out by Lazismu Solo through an economic empowerment program, namely the business development empowerment movement, is very well targeted. Implementation of productive zakat utilization Lazismu Solo provides assistance in the form of business capital assistance to mustahik. The provision of business capital assistance can have a positive impact and can prosper the mustahik economy